ChemInform Abstract: Homojesterones: Vinylogous Analogues of Jesterone from Helminthosporium velutinum TS28. Issue 24 (27th May 2016) - Arayama, Miki; Uesugi, Shota; Tanaka, Kazuaki; Maeda, Hayato; Nehira, Tatsuo; Kimura, Ken‐ichi; Hashimoto, Masaru
Abstract: isolation and structure elucidation of trans‐ and cis‐homojesterones